SC42 Integration of simulation into the recruitment of an Acute Intervention Team nurses improves prediction of subsequent performance. (3rd November 2019) - Rayner, Danielle; Randles, Derek; Ward, Lisa
Abstract : Background: Simulation has been embedded across a range of health professional education, and has been used in recruitment with some success¹, however the evidence of overall effectiveness in assessment is limited². We recently developed an Acute Intervention Team of band 6 nurses within our institution. In the process of recruitment we hypothesised that a single standardised high fidelity simulation scenario in addition to traditional interview would aid in selecting the candidates with the greatest aptitude for this role. Simulation provides a means to demonstrate non-technical skills which have been found to underpin good performance in acute clinical situations¹. Summary of project: Twenty seven candidates undertook a standardised high fidelity simulation based on sepsis, alongside a traditional interview. Two independent markers assessed each candidate in the domains of information gathering, recognition, escalation and 'other non-technical skills' based on their performance in simulation. The 10 successful candidates were followed over a six month period to analyse the predictive power of their simulation score in terms of subsequent workplace performance. Data was collected from electronic patient record (EPR) software which records the various tasks allocated to and completed by each member of the acute intervention team. Numbers of tasks were corrected for those working less than full time. Data was also collected regarding the destination of successful candidates who left the role within 12 months following appointment. Summary of results: The highest performing candidate in simulation completed the greatest number of clinical tasks over the 6 month period. There was a positive linear correlation between both the combined and simulation scores and total number of tasks completed (figure 1 ). In contrast, there was no correlation between traditional interview score alone and number of tasks completed. The same positive trend was demonstrated when considering only complex tasks, such as reviews of patients with a high early warning score. Of those who left the role with the first 12 months, the candidate with the lowest simulation score returned to their previous employment and the candidate with the highest simulation score was promoted to a band 7 role. Conclusions: In appointment to an acute nursing healthcare role requiring a high degree of independent practice, a standardised simulation scenario may have greater predictive validity for subsequent performance than a traditional structured interview. This area justifies further development and evaluation. References: Gale, T, Roberts, M, Sice, P. 2010. Predictive validity of a selection centre testing non-technical skills for recruitment to training in anaesthesia. British Journal of Anaesthesia, 105(5), pp. 603–609. Ryall T, Judd B, Gordon C. 2016. Simulation-based assessment in health professional education: a systematic review. J Multidiscip Healthc . 9, pp. 69–82.